PENGARUH KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. CITRA MANDIRI CEMERLANG PRIMA - Muhammad Andre; Ahmad Hermanto (Jurnal Manajemen Bisnis Krisnadwipayana, 2021)
To determine the Effect of Organizational Commitment and Organizational Culture on Employee Performance PT. Citra Mandiri Cemerlang Prima. This research is included in the category of causal associative research using a quantitative approach. The research was conducted by distributing questionnaires to respondents, all of whom were employees of PT. Citra Mandiri Cemerlang Prima, while the research method uses partially and simultaneous linear regression analysis. The hypothesis states that partially or simultaneous organizational commitment and organizational culture have a positive and significant effect on employee performance of PT. Citra Mandiri Cemerlang Prima.